Phonological Mean Length of Utterance in 48-60-Month-old Persian-Speaking Children With Isfahani Accent: Comparison of Story Generation and Conversation Samples - Fatemeh Karimian; Roya Mohammadi; Zahra Bemani; Yalda Kazemi; Faranak Kianfar (Journal of Rehabilitation, 2022)
Objective Phonological Mean Length of Utterance (PMLU), a quantitative measure for assessing phonological skills, is a diagnostic and clinical criterion in phonological development. Moreover, it is an indicator showing the efficacy of the intervention. The PMLU is a word level measure that can be calculated on the child’s transcribed speech sample (transcription). To calculate PMLU, all consonants and vowels of the child’s produced words, and target words (standard production of words in native adults) are individually scored. The proportion of Whole-Word Proximity (PWP), another phonological quantitative measure, includes the ratio of the produced PMLU to the targeted word PMLU. PWP indirectly reflects the intelligibility of speech. Since languages are distinctive in syllabic and phonological structures, PMLU should be studied as a language-specific measure. PMLU has specifically been designed to assess phonological skills in spontaneous speech. Spontaneous speech sampling methods are advantageous since they consider the effect of morphological and syntactic skills, length, and complexity of words, and they could show the normal development of word complexity. This study was conducted to determine PMLU and PWP in 48 to 60 months old Persian-speaking children with Isfahani accents and to compare them in story generation and conversation sampling methods. The potential sensitivity of PMLU to growth was also examined. Materials & Methods This is an observational and cross-sectional study that was conducted for one year in 2016 in Isfahan City, Iran. A total of 100 children (51 boys and 49 girls) aged 48-60 months participated in story generation sampling, and 67 children (32 boys and 35 girls) participated in conversation sampling. The participants were selected from 261 kindergartens under the supervision of the Welfare Organization of Isfahan Province using the convenience sampling method. After completing the consent form and considering the inclusion criteria, conversation and story-generation samples were collected. Audio samplings were done in the same room using the same software (Clear Record Litev. 2.1). Raters transcribed the first 50 words of the recorded speech samples. Finally, we used the formula to calculate the target PMLU and child PMLU based on the normal production of an adult who speaks Persian with an Isfahani accent and the child’s production, respectively. To evaluate inter-rater reliability, raters randomly transcribed 20% of all samples to recalculate values. Participants’ story generation and conversation scores were entered into SPSS16 separately. The Kolmogorov-Smirnov test was used to examine the data distribution. Based on the data distribution, paired t-test and Wilcoxon test were used to compare measurements, and the Pearson and Spearman tests were used to investigate the associations. Results Child PMLU, target PMLU, and PWP measures of the story generation method were 8.794, 8.811, 0.998, and those of the conversation method were 9.068, 9.093, and 0.998, respectively. Correlation test results showed significant relationship between age and PWP in story generation (r=0.308) and conversation (r=0.313). Comparing child PMLU in story generation and conversation showed a significant relationship between child PMLU in both sampling methods (P=0.000). The result of the target PMLU comparison in two methods of story generation and conversation (P=0.000) was significant. PWP did not significantly differ between the two sampling methods (P=0.973). The inter-rater reliability was calculated at 0.70. Conclusion This study can be used as a basis for quantitative studies in the field of children’s phonological assessment using Persian whole words. However, longitudinal studies in different age groups with a high level of evidence in this field can convince therapists to use whole-word measures in clinics.